Zarządzanie wiedzą w służbie zdrowia na przykładzie grupy zawodowej pielęgniarek i położnych: Knowledge management in the health service on the example of the nurses and midwives professional group - Karpińska-Karwowska, Małgorzata; Zarzeczna-Baran, Marzena (Management and Administration Journal, 2021)
Intellectual capital is defined as knowledge "contained" in humans. The main components of this asset include skills of employees and their professional experience. Skillful management of the intellectual capital results in a measurable outcome, such as an increase in the value of intellectual capital, the ability to eliminate errors, the development of knowledge and increase of creativity. This applies to all businesses, including health care institutions. Their activities in this area are additionally bound up with legal issues, imposing the requirements of postgraduate training onto health professionals. This paper presents the types of postgraduate training carried out by nurses and midwives, the scale of this issue, on the example of the District Board of Nurses and Midwifes in Olsztyn. In conclusion, the improvement of qualifications of the staff is good for business and at the same time can be used as a motivational tool in the process of personnel management.